Distribution of Cataract Surgical Rate and Its Economic Inequality in Iran. Issue 6 (June 2015) - Hashemi, Hassan; Rezvan, Farhad; Fotouhi, Akbar; Khabazkhoob, Mehdi; Gilasi, Hamidreza; Etemad, Koroush; Mahdavi, Alireza; Mehravaran, Shiva; Asgari, Soheila
ABSTRACT Purpose To determine the distribution of the cataract surgical number per million population per year (CSR), the CSR in the population older than 50 years (CSR 50+) in the provinces of Iran, and their economic inequality in 2010. Methods As part of the cross-sectional 2011 CSR survey, the provincial CSR and CSR 50+ were calculated as the total number of surgeries in major and minor centers divided by the total population and the population older than 50 years in each province. Economic inequality was determined using the average province income, the average urban and rural household incomes, and the percentage of urban and rural population in each province. Results Tehran and Ilam provinces had the highest and lowest CSR (12, 465 vs. 359), respectively. Fars and Ilam provinces had the highest and lowest CSR 50+ (71, 381 vs. 2481), respectively. Low CSR (<3000) was detected in 9 provinces where 2.4 to 735.7% increase is needed to reach the minimum required. High CSR (>5000) was observed in 14 provinces (45.2%) where rates were 0.6 to 59.9% higher than the global target. Cataract surgical rate increased at higher economic quintiles. Differences between the first, second, and fifth (poorest) quintiles were statistically significant. The CSR concentration index was 0.1964 (95% confidence interval, 0.0964 to 0.2964). Conclusions In line with the goals of the Vision 2020 initiative to eliminate cataract blindness, more than 70% of geographic areas in Iran have achieved the minimum CSR of 3000 or more. However, a large gap still exists in less than 30% of areas, mainly attributed to the economic status.